The Correlation of Family Support on Blood Sugar Levels in Diabetes Mellitus (DM) Sufferers - Nandang Jamiat; Salami Salami; Angga Wilandika; Fatimah Binti Sham (Journal of Public Health Sciences, 2026)
Diabetes Mellitus (DM) is closely linked to unhealthy dietary habits and sedentary lifestyles. Despite the efforts of the Indonesian government to manage DM through its chronic disease management program, many patients continue to experience poor glycemic control. Families, particularly primary caregivers, play a critical role in supporting patients with DM. This study aimed to analyze the correlation between family members' knowledge and attitudes toward family health tasks and glycemic control (fasting blood glucose levels) in DM patients participating in the Chronic Disease Management Program (CDMP) at a public health center in Bandung, Indonesia. A cross-sectional correlational study was conducted using a quantitative design. The study involved 65 family members who served as primary caregivers for DM patients, selected through a total sampling technique. Data were gathered using structured questionnaires to assess family members' knowledge and attitudes, along with clinical data on the patients' glycemic control. The relationship between variables was analyzed using the Spearman Rank Correlation test. The findings revealed no significant relationship between family members' knowledge and attitudes regarding caregiving tasks and the glycemic control of DM patients. Specifically, family knowledge and attitudes were not significantly associated with patients' glycemic control (p > 0.05). This study concluded that family members' knowledge and attitudes do not significantly influence glycemic control in patients with DM. These findings suggest that other factors may affect blood sugar levels, indicating the need for further research on family-based interventions and additional variables that could impact glycemic management.